Benzo[1, 2‐c;4, 5‐cʹ]bis[1, 2, 5]thiadiazole‐porphyrin‐based near‐infrared dyes. (21st September 2021) - Liu, Yi; Wu, Shaofei; Gopalakrishna, Tullimilli Y.; Wu, Jishan
Abstract: Benzo[1, 2‐c;4, 5‐cʹ]bis[1, 2, 5]thiadiazole (BBT) has intrinsic diradical character and herein it is used to construct organic near‐infrared (NIR) dyes together with the aromatic porphyrin unit. Three BBT‐porphyrin hybrid dyes 1 –3 with different linkage modes are synthesized by Pd‐catalyzed Sonogashira cross‐coupling between meso ‐ethynylene porphyrin units and monobromo‐/dibromo‐ BBT, or through unexpected homocoupling between the BBT units. They all possess small open‐shell diradical character and display intense NIR absorption in the range of 800–1000 nm. They also exhibit amphoteric redox behavior. BBT‐based diradicaloids are thus good candidates for organic NIR dyes. Abstract : Benzo[1, 2‐c;4, 5‐cʹ]bis[1, 2, 5]thiadiazole (BBT) and porphyrin‐based dyes 1 –3 are synthesized. They all possess open‐shell singlet diradical character and consequently, they show intense near‐infrared absorption in 800–1000 nm spectral range and amphoteric redox behavior depending on the linkage mode. The studies demonstrate that BBT is an ideal building block to construct stable organic near‐infrared dyes with tunable wavelength.